Cosmic Acceleration in an Anisotropic Universe with Bulk Viscosity in f(Q,T) Gravity Theory - Narzary, M.; Dewri, M. (Journal of Scientific Research, 2026)
The f(Q,T) gravity theory has been studied in the context of a spatially homogeneous and anisotropic Bianchi type-VI space-time in the presence of bulk viscous fluid. The field equations are solved explicitly with the help of hyperbolic hybrid scale factor R = eat[tanh(t)]b. The non-linear functional forms of f(Q,T) gravity: f(Q,T) = Q + αQ2 + βT where Q and T are non-metricity scalar and trace of energy momentum tensor respectively is considered. Some physical and geometrical properties are calculated and plotted their graphs in terms of time. For the considered model it is found that the coefficient of bulk viscosity appears to be positive and decreases over time. The cosmological behaviour of energy density, effective pressure, Equation of state parameter, and deceleration parameter are quite in good agreement with recent findings of cosmology. The energy conditions of the model are also studied.